2021
DOI: 10.1155/2021/4438613
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed Oil Supplementation Augments Antioxidant Capacity and Alleviates Oxidative Stress: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Objective. Studies have reported controversial findings regarding the flaxseed oil effect on antioxidant status biomarkers. The present meta-analysis aimed to determine the impact of flaxseed oil on the serum level of biomarkers of oxidative stress. Methods. A systematic search was conducted up to November 2020 on PubMed, Embase, Web of Science, Scopus, and Cochrane Central Library. Random-effects model was employed to perform meta-analysis. Subgroup analysis was carried out to determine the effect across diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Total antioxidant capacity (TAC) is the measure of the amount of ROS removed by a test solution, being used to assess the antioxidant capacity of biological samples ( Rubio et al, 2016 ). Malondialdehyde (MDA) is used as a marker of free radical formation by lipid peroxidation ( Musazadeh et al, 2021 ). The production of free radicals leads to the translocation of the nuclear-factor-Kappa-B (NF-kB) molecule into the nucleus and the production of pro-inflammatory cytokines such as tumor-necrosis factor-alpha (TNF- α) and interleukin-6 (IL-6).…”
Section: Introductionmentioning
confidence: 99%
“…Total antioxidant capacity (TAC) is the measure of the amount of ROS removed by a test solution, being used to assess the antioxidant capacity of biological samples ( Rubio et al, 2016 ). Malondialdehyde (MDA) is used as a marker of free radical formation by lipid peroxidation ( Musazadeh et al, 2021 ). The production of free radicals leads to the translocation of the nuclear-factor-Kappa-B (NF-kB) molecule into the nucleus and the production of pro-inflammatory cytokines such as tumor-necrosis factor-alpha (TNF- α) and interleukin-6 (IL-6).…”
Section: Introductionmentioning
confidence: 99%
“…The antiinflammatory effects of flaxseed have been examined in two of the included studies in which flaxseed supplementation decreased CRP (Haidari et al, 2020; Mirmasoumi et al, 2018) and IL‐6 (Haidari et al, 2020). Recent meta‐analysis studies demonstrated that flaxseed could manifest potent antioxidant and antiinflammatory functions (Musazadeh et al, 2021; Tamtaji et al, 2020). Given that flaxseed is a rich source of polyphenols such as lignans, phenolic acids, flavonoids, phenylpropanoids, and tannins (Kasote, 2013), these observations are not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity is one of the most significant functions of PB because the scavenging process of antioxidants plays an important role in preventing the harmful effects of free radicals. It is well known that oxidative stress is associated with aging, inflammation, and cancer and can cause various chronic diseases including hypertension, diabetes mellitus, aging, and Alzheimer's disease [ 4 , 5 ]. PB crude extraction has been reported to possess a high antioxidant capacity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%